Dark Skies Places, Practices, Communities - Dunn, Nick; Edensor, Tim (Taylor & Francis, 2024)
Dark Skies addresses a significant gap in knowledge in relation to perspectives from the arts, humanities, and social sciences. In providing a new multi- and interdisciplinary field of inquiry, this book brings together engagements with dark skies from a variety of disciplinary backgrounds, empirical studies, and theoretical orientations. Throughout history, the relationship with dark skies has generated a sense of wonder and awe, as well as providing the basis for important cultural meanings and spiritual beliefs. However, the connection to darks skies is now under threat due to the widespread growth of light pollution and the harmful impacts that this has upon humans, non-humans, and the planet we share. This book, therefore, examines the rich potential of dark skies and their relationships with place, communities, and practices to provide new insights and understandings on their importance for our world in an era of climate emergency and environmental degradation. This book is intended for a wide audience. It will be of interest to scholars, students, and professionals in geography, design, astronomy, anthropology, ecology, history, and public policy, as well as anyone who has an interest in how we can protect the night sky for the benefit of us all and the future generations to follow.